KAJIAN ESTETIKA, FUNGSI, DAN MAKNA UANG KERTAS SERI TEUKU UMAR DAN CUT NYAK DIN - Anissa Mei Primasanthi; Nooryan Bahari; Sarah Rum Handayani (DeKaVe, 2017)
Money as a medium communication between ruler with his subjects so that all symbol reflect social conditions and culture. Aesthetic design currency series Teuku Umar and Cut Nyak Din represent symbols culture local knowledge of social values cultural and religious made money have a high art.